(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
An automatic transfer switch (ATS) automatically transfers electrical power from a primary to a backup supply during power failure. However, there are some inconsistencies associated with this transfer method. Therefore, this research designed, constructed, and tested an Arduino Uno R3 board-based ATS prototype for the automatic transfer of electricity. This model generally consists of electrical equipment, electronic devices, and programming software. Furthermore, a ladder diagram in SoapBox Snap software, integrated with IDE software used to test the prototype. The ac relays were for the main and generator supply sensors, while the dc relays were for the generator switching, starting, and stopping processes. Basically, the capacities of the components for the main and backup generator supplies were based on 900 VA, 220 volts, 4.09 ampere, and 50 Hz for power, voltage, current, and frequency, respectively. Four functional tests were conducted on a normal, main supply outage, generator failure, and main supply conditions. The result showed that the main-to-backup supply switching time was 15.13 seconds, close to the standard time of 15 seconds. The average statistical error was 1.11% and was used as a third-class category of measuring instruments. Meanwhile, the operational voltage range was between 135 volts and 245 volts on loading conditions.